2021
DOI: 10.3390/cancers13133320
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Surgical Resection and Reasons for Poor Prognosis of Pelvic Osteosarcoma Based on the Bone Tumor Registry in Japan

Abstract: Pelvic osteosarcoma has a poor prognosis compared to osteosarcomas in other locations, and the reasons for this remain unknown. Surgical resection of pelvic osteosarcoma is technically demanding and often results in dysfunction and complications. In this study, we investigated the reasons underlying the poor prognosis of pelvic osteosarcoma by comparing it to femoral osteosarcoma using data from the Bone Tumor Registry in Japan. We used propensity score analysis to determine whether surgical resection of pelvi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 27 publications
0
14
0
Order By: Relevance
“…Numerous studies have reported that as the height of an individual increases so does the risk of OS [ 17 19 ]. Pelvic osteosarcoma has a substantially worse prognosis than osteosarcoma of the extremities [ 20 ]. This study also confirmed the AJCC stage was an independent risk factor that affected the prognosis of OS patients.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have reported that as the height of an individual increases so does the risk of OS [ 17 19 ]. Pelvic osteosarcoma has a substantially worse prognosis than osteosarcoma of the extremities [ 20 ]. This study also confirmed the AJCC stage was an independent risk factor that affected the prognosis of OS patients.…”
Section: Discussionmentioning
confidence: 99%
“…Osteosarcoma is the most common primary bone tumor in children and young adults (104)(105)(106)(107)(108). However, the overall survival of patients with osteosarcoma remains unfavorable despite attempts to improve the efficacy of chemotherapy (109)(110)(111). Recent studies have proposed that targeting lncRNAs may provide a novel insight into the treatment of osteosarcoma (112)(113)(114)(115).…”
Section: Osteosarcomamentioning
confidence: 99%
“…The prognosis for OS patients with axial bone site affliction, such as the spine and pelvis, is considerably poorer compared to their counterparts suffering from limb‐related OS. Patients with metastases in the lungs or other regions, along with those exhibiting inadequate response to chemotherapy, tend to have a dismal prognosis 5,6 . Consequently, there is an exigent requirement for devising precise and dependable biological methodologies for predicting OS diagnosis and prognosis.…”
Section: Introductionmentioning
confidence: 99%
“…Patients with metastases in the lungs or other regions, along with those exhibiting inadequate response to chemotherapy, tend to have a dismal prognosis. 5,6 Consequently, there is an exigent requirement for devising precise and dependable biological methodologies for predicting OS diagnosis and prognosis.…”
mentioning
confidence: 99%